SAT0398 Pregnancy outcomes in korean women with ankylosing spondylitis. (15th June 2017) - Park, EH; Jun, JK; Lee, SM; Song, YW; Lee, EB
Abstract : Background: Ankylosing spondylitis (AS) is a chronic, systemic, inflammatory disease that primarily affects the sacroiliac joints and spine. Despite overwhelming prevalence of AS in men, it can also occur in women. Since AS mainly affects the sacroiliac joints, a special attention should be paid to the normal labors and pregnancy outcomes in these female patients. However, very little is known about the impact of AS on pregnancy outcomes due to rare occurrence of the disease in women. Objectives: To investigate the pregnancy outcomes in Korean female patients with AS. Methods: All of the 27 deliveries from 20 AS female patients who had been cared at Seoul National University Hospital between February 1994 and June 2016 were retrospectively evaluated through medical record review. After matching each pregnancy of the AS women with the pregnancies of the control group on a 1 to 4 ratio based on maternal and gestational age, pregnancy outcomes of AS patients were compared with those of the control group. Pregnancy outcomes included cesarean section (CS) rate, preterm birth, low birth weight infant, fetal growth restriction (FGR), fetal malformations and preeclampsia. Each pregnancy was considered as a separate observation, and outcomes between the groups were compared by regression models estimated using Generalized Estimating Equations (GEEs) to account for the matched nature of the data. For zero events in either group in which GEE models do not converge, Fisher's exact test or Chi-square test were used. Results: Caesarean section (CS) was performed in 44.4% of deliveries among women with AS compared with 20.4% in controls (p=0.002) (Table 1 ). The indications of CS included previous uterine surgery, breech position, placenta previa, placental abruption, fetal distress, and cephalopelvic disproportion (CPD), which were comparable between two groups. When excluding the cases of elective CS, 16 pregnant women with AS were tried for the vaginal delivery. Among them, 15 cases (93.8%) achieved successful vaginal deliveries, which was comparable to the successful vaginal delivery rate in controls (86/90 (95.6%), p=0.566). CS due to CPD was done in 1 case (8.3%) of AS women, while there was no case in the controls (p=0.353). Interestingly, the severity of sacroiliitis in AS patients did not show any association with CS (p=0.342). Women with AS had a higher frequency of LBW compared to the controls (22.2% vs 8.3%, p=0.024). However, there was no statistically significant difference in other adverse pregnancy outcomes, including preterm birth, FGR, fetal malformations, and pre-eclampsia. Conclusions: Although pregnant women with AS are concerned about CPD during their labors due to the involvement of the sacroiliac joints, vaginal deliveries can be tried in patients with AS. The obstetric and perinatal outcomes in women with AS were also comparable to normal pregnant women. Disclosure of Interest: None declared